School closures and student achievement, evidence from a high stakes exam - Marc Riudavets-Barcons; Roope Uusitalo (Helsinki Graduate School of Economics, 2023)
We study the effect of school closures and the transition from on-site to on-line teaching during the Covid-19 pandemic in the Finnish upper secondary schools. To identify the effects we exploit variation in the length of school closure periods across schools between autumn 2020 and spring 2021. Using a difference-in-difference design, we show that the students who studied on-line for longer periods performed equally well in the Matriculation exam at the end of upper-secondary education than the students who experienced shorter school closures. Moreover, we show that inequalities across Finnish students from different socioeconomic backgrounds did not exacerbate during this period.
Keywords: I21; I24; I28; 330; school closures; online teaching; test scores